Females Are Less Likely Invited Speakers to the International Stroke Conference: Time's Up to Address Sex Disparity. Issue 2 (February 2020) - Fournier, Lauren E.; Hopping, Grant C.; Zhu, Liang; Perez-Pinzon, Miguel A.; Ovbiagele, Bruce; McCullough, Louise D.; Sharrief, Anjail Z.
Abstract : Supplemental Digital Content is available in the text.